Innovative Scientific and Practical Approaches to Biodiversity Conservation in Uzbekistan: Digital Ecology and Nature‑Based Solutions for Sustainable Development - Naaz, Sofia; qizi, Najmiddinova Nilufar Nurali (American Journal of Biology and Natural Sciences, 2026)
Biodiversity in Uzbekistan, encompassing deserts, steppes, riparian forests, wetlands, and mountain ecosystems, is increasingly threatened by climate change, water scarcity, land degradation, and unsustainable land use. This study evaluates an integrated conservation framework that combines digital ecology tools (remote sensing, GIS, artificial intelligence, and predictive modeling) with nature-based solutions (NbS), including habitat restoration, ecological corridors, wetland rehabilitation, and community participation. Between 2022 and 2025, twelve pilot sites across five ecological regions were monitored. Spatial analysis identified 174 biodiversity hotspots, 38 critical habitats outside protected areas, and 22 high-risk degradation zones. AI-assisted monitoring achieved 93% accuracy across 45 target species. NbS implementation resulted in a 28–44% increase in vegetation cover, a 22% improvement in soil moisture, and the return of endangered species in 67% of restored sites. Predictive models indicate that without intervention, 24% of habitats may lose suitability by 2040, while integrated digital-NbS strategies could preserve over 80%. The results confirm that combining digital technologies with NbS provides an effective, scalable, and climate-resilient approach to biodiversity conservation in Uzbekistan.